TINJAUAN PENGARUH LETAK BUKAAN TERHADAP PERSEPSI PENGHUNI PADA GEREJA-GEREJA DI INDONESIA - Cornelia Hildegardis (ITB Ahmad Dahlan Jakarta, 2022)
The research was conducted to examine the location of the openings in several churches in Indonesia against the views of the residents who were in them. The location is determined based on the koppen climate classification for tropical regions in Indonesia which is divided into tropical rain forests, tropical monsoons, and savanna. The study was conducted by comparing previous studies on churches in Indonesia. The results from the three tropical regions concluded that occupant distance, dimensions, and conditions of openings (open/closed) were able to influence the perception of comfort felt in the building.